Growth rate and yield of water spinach (Ipomoea reptans) under three watering systems - Isnar, Mohd Syarbani (2019)
The irrigation system (overhead sprinkler, drip irrigation, and a capillary wick system) determines the water supply to water spinach (Ipomoea reptans) where water is an adequate element for their growth rate. The main problem for the irrigation system is water loss/wastage. Overhead sprinkler will have the most amount of water loss. The drip irrigation system has irregular water pressure. A capillary wick system does not have much water loss, where it is lost by evaporation process in the PVC pipe. The seeds are directly sown in the Rb900 tube, replacing the polybag. Rb900 tube is made of plastic one alternative way because the tube is lighter and uses less media. The tube system however has not been tested scientifically. The media use was BX-1, but the problem with the media is its nutrient content are not known. The objective of this project was to compare three irrigation systems (overhead sprinkler, drip irrigation, and a capillary wick system) in term of their effects on: i) Water spinach leaf nutrient contents (N, P, K, Ca, and Mg), ii) Growth rate of water spinach under three different watering system, and iii) BX-1 media analysis. The field experiment was located at Field No. 15, University Putra Malaysia under a rain shelter. There were three replications per treatment. Consequently, the design comprises nine experimental units or plot. The experiment layout was the RCB (Randomized Complete Block) design. Each experiment plot consisted of a single tray or tube stand that accommodated 10 water spinach (Ipomoea reptans) seedlings, where each seedling planted in a RB900 rubber tube and with BX-1 as the growth media. The total number of water spinach was required at least 10 plants per plot x 9 plots or 90 plants. Irrigation was carried out daily. For all treatments except the capillary wick system, a daily total of 45 ml of water was supplied to each tube. Plant growth rate was measured once every 7 days until 28 days. A seedling from every plot was destructively measured. Growth parameter measured were the dry weight of the various plant part (leaves, stem, and roots), total leaf area, and plant height were increased proportional to the time. The leaf tissue samples were oven dried at 105˚C for 2 h and then analysed, following Jones (2001), for its nutrient status of the wet ashing method. These three treatments had significant effects on growth rate and yield of water spinach where capillary wick system, T3 show the highest growth rate and yield of water spinach due to less leached of water. The nutrients status decreased over times because of volatilizations of nutrients to the air and denitrification occurred.